Diversity of Contaminants Fungi in Coffee Beans Stored Using Polystyrene and Gunny Sacks in South OKU Regency (Indonesia) - Deli Lilia; Nurhayati Damiri; Mulawarman Mulawarman (Sriwijaya Journal of Environment, 2021)
Robusta coffee is a coffee type found in South OKU Regency in Indonesia, and its storage process is highly susceptible to the growth of various fungal species, including fungi that produce Ochratoxin A (OTA). Therefore, this study aims to examine the fungal contamination contained in storage using polystyrene and gunny sacks for 20 and 30 days. Data were obtained from surveys, interviews, and samples from 30 farmers which stored coffee beans using polystyrene and gunny sacks in May-July 2020. The results showed that the moisture content was higher in storage using gunny sacks than in polystyrene sacks, at 16.94 ± 0.878 % and 15.99 ± 1.33%, respectively. Furthermore, 16 fungal species were present in gunny sack storage, while 14 fungal species were observed in polystyrene sacks. The percentage of OTA-producing fungi A.niger and A.ochraceus in the two stores yielded 100% and 63.3%, respectively